Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/imb.12767
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of sphingomyelinase (NlSMase) causes ovarian malformation of brown planthopper,Nilaparvata lugens(Stål)

Abstract: Sphingomyelinases (SMases) are a group of enzymes that catalyse the hydrolysis of sphingomyelins into ceramides and phosphorylcholine. They have been intensively investigated for their pathophysiological roles in mammals whereas much remains unclear about their counterparts in insects. Herein we report the cloning and functional characterization of four SMase homologue genes, designated NlSMase1‐4, from brown planthopper (BPH). The phylogenetic analysis revealed that NlSMase1 and NlSMase2 were clustered into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…In addition, Vg has also been reported to be synthesized in follicular cells, nurse cells, and haemocytes [ 5–7 ]. Cumulative studies have demonstrated that female reproduction is regulated by numerous biological and abiotic factors, such as hormones, environmental temperature, nutrition, and metabolism [ 8–10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Vg has also been reported to be synthesized in follicular cells, nurse cells, and haemocytes [ 5–7 ]. Cumulative studies have demonstrated that female reproduction is regulated by numerous biological and abiotic factors, such as hormones, environmental temperature, nutrition, and metabolism [ 8–10 ].…”
Section: Introductionmentioning
confidence: 99%